Penentuan Masa Tanam Jagung (Zea mays L.) Berdasarkan Curah Hujan dan Analisis Neraca Air di Kabupaten Pohuwato - Musa, Nikma (Jurnal Agroteknotropika, 2012)
The aimed of this research was to determining of maize growing periods based on rainfall and water balance analysis in Pohuwato Regency. Identify agro-climate and climate interpretation of data based on years of observation during 1994-2008. The evapotranspiration using methods Blaney-Criddle measured with the water temperature and latitude as prime criterions. The result showed that the annual rainfall was 1.382 mm-1 year. Variations in rainfall ranges from 48.40 mm to 203.11 mm. the lowest rainfall in August and highest in January. The results of calculation of the year every decade showed that the highest rainfall is in the third decade (75.78 mm) in January and the lowest rainfall is in the decade of 23, 24, 26, 27, 29 (11-16 mm) in August, September and early October. Data obtained from the calculated potential evapotranspiration, the highest 60, 64 mm/decade or 170.903 mm/month. Based on the analysis of water balance 0.5 ETP and rainfall (P), then look rainfall values exceeding 0.5 ETP in January until mid-July and early November to December, so that in the months that have a surplus of water, with thus in the months which will serve as the initial basis of the growing season. Late July to late October water deficit. The analysis showed Plant period available for the maize crop in the region Pohuwato in November too early or mid-July and planting can be done three times by the age of the plant is 80-110 days.